Drive Distraction and Risky Driving Behavior: A Meta-analysis Study - Gabriela Hamazia Manuhutu; Jusuf Tjahjo Purnomo (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study fills a research gap by extending previous studies on driver distraction and risky driving behavior beyond specific contexts or distraction types. This meta-analysis assesses the strength of the relationship, heterogeneity, publication bias, and moderators. The literature was searched through PubMed, ScienceDirect, and Elsevier (2015-2025). Of 128 articles, 10 cross-country studies with samples of 165-21,000 respondents passed PRISMA selection. Random-effects analysis with Fisher’s z transformation showed a heterogeneity (I² = 99.63%; Q = 2394.305; p < .001). Publication bias tests (Fail-safe N = 12,234; Egger p = 0.861; Begg p = 0.381; trim-and-fill = 0) showed no bias, and the association between variables remained consistent. Visual, manual, and cognitive distractions increase risky driving behavior. Findings support educational policies, stricter regulations, and distraction-mitigation technologies, and offer novelty in synthesizing the latest cross-national evidence. Keywords: drive distraction, risky driving behavior, meta-analysis, traffic safety, driver attention